“Efecto del Ascophyllum nodosum combinado con ácidos húmicos y fúlvicos, sobre el rendimiento del cultivo de maíz (Zea mays L.)” - Sánchez Botto, Juan José (2019)
VIII. SUMMARY The present experimental work was carried out in the grounds of Mrs. Tanny Sánchez Botto, located in the El Carbon enclosure, belonging to the parish of Isla de Bejucal, Baba Canton. The geographical coordinates are 110597,97 UTM south latitude and 277 438,26 UTM west longitude and 8 msnm. The thunder corn hybrid was used as seed material, the treatments studied were Stimplex in doses of 0,75 and 1,0 L/ha; Lonite 0,75 and 1,0 L/ha; Stimplex + Lonite dose of 0,75 + 0,75; 0,75 + 1,0; 1.0 + 0,75; 1,0 + 1,0 L/ha plus a treatment without product (Control), using the experimental design of Complete Blocks at Random with 9 treatments and 3 repetitions. To perform the evaluation of the means of the treatments, the Tukey test was used at 95% probability. The plots had a dimension of 5,0 m wide x 6,0 m long, giving a total area of 900 m2. For the execution of the trial all the practices and agricultural work that the crop requires for its normal development were carried out, such as soil analysis, land preparation, sowing, weed control, phytosanitary control, fertilization, irrigation, harvest. Based on the results obtained, it was determined that the alga Ascophyllum nodosum combined with humic and fulvic acids positively influenced the performance of the corn crop (Zea mays L.); the agronomic characteristics of height of plant and insertion of the ear, diameter and length of ear, number of grains per ear and weight of 1000 grains obtained excellent averages using Stimplex + Lonite, in doses of 1,0 + 1,0 L/ha ; the yield of the crop reached high averages, however it stood out the application of Stimplex + Lonite, in doses of 1,0 + 1,0 L/ha with 7462,2 kg/ha and in the economic analysis, the use of Stimplex + Lonite, in a dose of 1,0 + 1,0 L/ha, allowed obtaining the highest net benefit with $ 623,5. Key words: alga, Ascophyllum nodosum, humic acids, fulvic acids, corn.